SISTEM INFORMASI PENGENALAN PAKAIAN ADAT TRADISIONAL INDONESIA BERBASIS WEB - Darsin, Darsin; Ngajiyanto, Ngajiyanto (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Indonesia is an archipelagic country that is rich in a variety of cultural products, one of which is traditional clothing. However, as time goes by, the preservation of traditionals clothing is increasingly being eroded by foreign cultures and increasingly being forgotten by today's younger generation. Making an information system that displays various kinds of traditional clothing is an alternative media for introducing Indonesian traditionasl clothing. The method used in the development of this information system uses the waterfall model where the data collection techniques used include interviews and literature study. This information system was developed using the programming language PHP (Hypertext Prepocecor) and MySql database. The design is built using HTML and CSS. The author hopes that this information system can publish information quickly and accurately to the public in finding information about traditional custom clothing. The purpose of this research is to build a web-based information system to display traditionals clothing starting from brief information, history or origins as well as online galleries of traditionals clothing.